Mengembangkan Perangkat Pembelajaran Kalkulus Integral Berbasis Model Pengajuan dan Pemecahan Masalah untuk Meningkatkan Kemampuan Berpikir Kreatif Mahasiswa - Waluyo, Edy; Supiyati, Sri; Halqi, Muhammad (Jurnal Elemen, 2020)
This study aims to develop learning set in the Integral calculus in the form of instructional design or study the concept of the volume of an Integral calculus rotating object that has a potential effect in improving student creative thinking skills based on model submission and problem-solving. The study used the Borg and Gall model development research with the stages of the development of learning design ranging from analysis, design, development, implementation, and evaluation. This study used the subject of 34 students of the University of Mathematics Education Study Program Hamzanwadi, which programmed the Integral calculus course consisting of 6 males and 28 females. Data collection using product guidelines or product validation sheets, product practices, and posttests to measure practicality and potential effects product. From the results of the data analysis, instructional design is drafted and designed based on the filing and problem-solving model of products that meet the criteria of validity, practicality, and effectiveness of products and feasible to implement. The product developed is also a potential in enhancing the students' creative thinking skills with a N-Gain of 0.73.